Analisis Pengaruh Rotasi Kerja, Mutasi Kerja Dan Gaya Kepemimpinan Terhadap Efektivitas Kinerja Karyawan BPJS Ketenagakerjaan Wilayah Sulawesi-Maluku - Randi Ariady Suwardi; Basri Modding; Nurhayati Azis (Departement of Mathematics Education, 2023)
performance effectiveness; (2) Mutations have a positive and significant effect on performance effectiveness; and (3) Leadership Style has a positive and significant influence on the performance effectiveness of the employees of the Sulawesi - Maluku Region Employment BPJS. This means that job rotation is supported by the ability to complete work, experience and insight, adequate level of knowledge, high work performance. Then the implementation of mutations is objectively related to the accuracy of the position according to the level of education, career opportunities are based on ability. Furthermore, leadership style with the ability to make decisions, able to motivate, be communicative, able to control subordinates, responsible and able to control emotions. The independent variable with its indicators can encourage the achievement of employee performance effectiveness which is useful for the development of work productivity at the Sulawesi - Maluku Region Employment BPJS. Research Recommendations: (1) The need for Employment BPJS to play an active role in controlling, directing, guiding, and increasing cooperation among fellow employees; (2) So that BPJS Ketenagakerjaan carries out objective mutations or according to the rules and criteria that have been determined.